Active vibration control of non-determinic subsystem using piezoelectric patch actuator - Azni Nabela Wahid (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Vibration control using piezoelectric (PZT) material has gained significant attention for its ability to behave as a sensor or actuator due to PZT direct and inverse effect. For control or excitation purposes, PZT patch actuator is embedded or attached on engineering built-up structures. Engineering systems such as aircraft, ships and automotive are considered built-up structures and dynamically they are thought of as being fabricated from many components that are classified as deterministic structure (DS) and non-deterministic structure (Non-DS). Adding a PZT actuator on a structure is equivalent to adding an external moment to the dynamics of the structure. However, the influence of adding input moment to a Non-DS is not fully understood due the complexity of the resulting wave; no mathematical representation has been established. In order to apply SEA method for input moments, a mathematical representation for moment generated by PZT patch in the form of average power is needed; so that a control system can be implemented. In this research, a simply-supported plate attached with a PZT patch is taken as a benchmark model. Ensemble average of power given by the PZT patch actuator to the plate when subjected to structural uncertainties is simulated using Lagrangian method and Monte-Carlo simulation. In addition, it is found out that the mathematical solution to estimate average power delivered to a structure can also be represented by mobility function. The findings of the research discovered that using moment mobility equation for a thin plate excited by a force couple, the power delivered by PZT actuator to a non-deterministic plate can be well-represented, particularly at high frequency range, therefore drastically cut computation time and cost. Parametric studies show that changing the patch location on the structure will not affect the ensemble average power supplied at high frequency. On the contrary, changing the patch size will change the power magnitude proportionally. In the second part of the thesis, the optimal gain values for a PZT patch controller in order to achieve maximum energy reduction for a non-deterministic thin plate is obtained using the Hybrid modelling method and mobility function. It is theoretically shown that by using larger numbers of point controllers on a Non-DS, better control effect can be achieved. A concluding remark can be made that findings from this research can be applied in SEA and the hybrid method used for analysing and vibration control of complex built-up structures.